Antifungal susceptibility testing in Candida, Aspergillus and Cryptococcus infections: are the MICs useful for clinicians?. (August 2020) - Bassetti, M.; Vena, A.; Bouza, E.; Peghin, M.; Muñoz, P.; Righi, E.; Pea, F.; Lackner, M.; Lass-Flörl, C.
Abstract: Background: Invasive fungal infections (IFIs) represent a global issue and affect various patient populations. In recent years, resistant fungal isolates showing increased azole or echinocandin MICs have been reported, and their potential clinical impact has been investigated. Aims: To provide an update on the epidemiology of resistance among fungi (e.g., Candida spp., Aspergillus spp., and Cryptococcus spp.) and to offer a critical appraisal of the relevant literature regarding the impact of MICs on clinical outcome in patients with IFI. Sources: PubMed search with relevant keywords along with a personal collection of relevant publications. Content: Although antifungal resistance has been associated with a poorer response to antifungal therapy in various studies, other factors such as comorbidities, septic shock and source of infection appear to be key determinants affecting the clinical outcome of patients with IFI. Implications: Future international collaborative studies are required to tease out the relative contribution of in vitro antifungal resistance on patient outcomes, thus enabling the optimization of IFI management.